Diskriminasi Penegakan Hukum Bagi Masyarakat Golongan Tertentu di Indonesia - Muhammad Ezzat Everoes; Andi Nur Alawani Kalsum; Raissa Frieda Garnetavegi; Safira Putri; Muhammad Ilham Duata; Khaila Aurellia; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Indonesia is known as a vast country with a large population. Due to this, the government uses the legal system that has brought many conveniences by regulating and bringing justice to the problems that are encountered in people's daily lives. A large number of law enforcement agencies are formed to balance the number of people that need it. This looks like a good thing. With the large number of law enforcement in Indonesia the conveniences of seeking help due to legal matters can be spread evenly throughout the people. However, a large number of discrimination in law enforcement among different classes and hierarchy has been found. Taking from these problems, the writing of this article aims to find out the discrimination that occurs in law enforcement in Indonesia and analysis of discrimination cases against students in Surabaya. The method used in this writing is a qualitative method combined with literature study techniques in collecting data. The results of this essay explain the existence of the phenomenon of discrimination in law enforcement in Indonesia, the chronology of solving the problem of legal discrimination by Papuan students in Surabaya.. The conclusion of this study is Discrimination in law enforcement occurs because of irresponsible officials, aspects of discrimination in law enforcement in Indonesia are social stratification, morphology and cultural differences, the actions of these individuals are contrary to Article 5 UU issue 40 2008 concerning the Elimination of Racial and Ethnic Discrimination.